Combined MPM-DEM for Simulating the Interaction Between Solid Elements and Fluid Particles. (27th March 2017) - Yang, Youqing; Sun, Pengtao; Chen, Zhen
Abstract: How to effectively simulate the interaction between fluid and solid elements of different sizes remains to be challenging. The discrete element method (DEM) has been used to deal with the interactions between solid elements of various shapes and sizes, while the material point method (MPM) has been developed to handle the multiphase (solid-liquid-gas) interactions involving failure evolution. A combined MPM-DEM procedure is proposed to take advantage of both methods so that the interaction between solid elements and fluid particles in a container could be better simulated. In the proposed procedure, large solid elements are discretized by the DEM, while the fluid motion is computed using the MPM. The contact forces between solid elements and rigid walls are calculated using the DEM. The interaction between solid elements and fluid particles are calculated via an interfacial scheme within the MPM framework. With a focus on the boundary condition effect, the proposed procedure is illustrated by representative examples, which demonstrates its potential for a certain type of engineering problems.